Prevalencia de Giardia lamblia en escolares y en otras subpoblaciones peruanas (1990-2018): una revisión sistemática y metaanálisis - Cabrera, Rufino (2023)
The study aimed to determine the prevalence and distribution of Giardia lamblia in the Peruvian population between 1990 and 2018. A systematic review and meta-analysis of cross-sectional studies was carried out. It was included original studies on the prevalence of G. lamblia, intestinal parasitism or cohort studies that included prevalence data, and diagnosed by parasitological examination, antigen detection, PCR or genetic analysis, published between 1990 and 2018 in Spanish, English, Portuguese or French and carried out in humans. Searches were performed in PubMed, Scopus, LILACS, SciELO, LIPECS, Google Scholar, and ALICIA. Analysis of heterogeneity was performed using Cochrane's Q test and publication bias using Egger's method with StatsDirect v. 3.2.7. The analysis included 33 sources that had information from 37 studies involving 10 109 individuals. The combined prevalence by the random effects method in the 37 studies was 30.4% (CI 95% 25.2-35.8); however, when analysing the subgroup in pre-schoolers and schoolchildren in 26 studies it was 29.1% (CI95% 24.5-34.0). Of every 100 people, 30 had G. lamblia and of every 100 pre-schoolers and schoolchildren, 29 had the parasite. Prevalence estimates according to sex and area of residence are not conclusive. Not enough studies were found in 7 other subpopulations to estimate the prevalence of G. lamblia.